Influence of Outer Surface Protein A Antibody on Borrelia burgdorferi within Feeding Ticks - de Silva, Aravinda M. (American Society for Microbiology, 1999)
Borrelia burgdorferi, the spirochetal agent of Lyme disease, is transmitted by Ixodes ticks. When an infected nymphal tick feeds on a host, the bacteria increase in number within the tick, after which they invade the tick’s salivary glands and infect the host. Antibodies directed against outer surface protein A (OspA) of B. burgdorferi kill spirochetes within feeding ticks and block transmission to the host. In the studies presented here, passive antibody transfer experiments were carried out to determine the OspA antibody titer required to block transmission to the rodent host. OspA antibody levels were determined by using a competitive enzyme-linked immunosorbent assay that measured antibody binding to a protective epitope defined by monoclonal antibody C3.78. The C3.78 OspA antibody titer (>213 μg/ml) required to eradicate spirochetes from feeding ticks was considerably higher than the titer (>6 μg/ml) required to block transmission to the host. Although spirochetes were not eradicated from ticks at lower antibody levels, the antibodies reduced the number of spirochetes within the feeding ticks and interfered with the ability of spirochetes to induce ospC and invade the salivary glands of the vector. OspA antibodies may directly interfere with the ability of B. burgdorferi to invade the salivary glands of the vector; alternately, OspA antibodies may lower the density of spirochetes within feeding ticks below a critical threshold required for initiating events linked to transmission.